Through the eyes of the student: Best practices in clinical facilitation - Immaculate S. Muthathi; Catherine H. Thurling; Susan J. Armstrong (AOSIS, 2017)
Background: Clinical facilitation is an essential part of the undergraduate nursing curriculum. A number of studies address the issue of clinical facilitation in South Africa, but there remains a lack of knowledge and understanding regarding what students perceive as best practice in clinical facilitation of their learning. Objective: To determine what type of clinical facilitation undergraduate students believe should be offered by clinical facilitators (nurse educators, professional nurses and clinical preceptors) in the clinical area in order to best facilitate their learning. Method: A qualitative, exploratory and descriptive study was conducted. Purposive sampling was performed to select nursing students from the second, third and fourth year of studies from a selected nursing education institution in Johannesburg. The sampling resulted in one focus group for each level of nursing, namely second, third and fourth year nursing students. Interviews were digitally recorded and transcribed verbatim, thematic data analysis was used and trustworthiness was ensured by applying credibility, dependability, confirmability and transferability. Main findings: The data revealed that participants differentiated between best practices in clinical facilitation in the clinical skills laboratory and clinical learning environment. In the clinical skills laboratory, pre-contact preparation, demonstration technique and optimising group learning were identified as best practices. In the clinical learning environment, a need for standardisation of procedures in simulation and practice, the allocation and support for students also emerged. Conclusion: There is a need for all nurses involved in undergraduate nursing education to reflect on how they approach clinical facilitation, in both clinical skills laboratory and clinical learning environment. There is also a need to improve consistency in clinical practices between the nursing education institution and the clinical learning environment so as to support students' adaptation to clinical practice.